Positivization of Sharia Regional Regulations in North Sumatra - Irwansyah, Irwansyah; Ananda, Faisar; Zulham, Zulham (Jambura Law Review, 2021)
The inability of the law to be an accommodating and acceptable rule makes for disharmony over diversity in Indonesia. Various sharia-nuanced regional regulations continue to emerge in various regional lines in Indonesia. However, it is necessary to conduct legal analysis related to its existence in the constitutional legal system in Indonesia. The research method used is normative juridical. The results showed that in a democratic country positivization of Islamic law both in absolute (law) and relatif  (local regulations) does not violate in the constitutional legal system that also guarantees the fulfillment of human rights to its citizens. In addition, the lack of political will from the regional government of North Sumatra to support sharia-nuanced regional regulations proposed by districts / cities that are less responded to by the government at the provincial level that hinders the process of positivization of sharia-nuanced regional regulations in North Sumatra